Resistance of Fry from Vaccinated Mother of Gift Tilapia (Oreochromis niloticus Linn.) to Artificial Infection of Streptococcus iniae - Nur, I.; Sukenda, .; Dana, D. (Jurnal Akuakultur Indonesia, 2004)
An investigation was made to study the efficacy of dosage and time of administration in maternal vaccination. Mothers of nile tilapia were vaccinated by intraperitoneal injection with adjuvant-heat killed Streptococcus iniae at one and two weeks after spawning at the dosages of 0,2 ml/kg and 0,4 ml/kg body weight. Unvaccinated mothers were used as control. Agglutinating antibody titers in the blood plasma of mothers before and after spawning, eggs soluble extract, the body fluid of fry at 5, 10 and 15 days post hatching (DPH) were examined. The protective immunity of fry was tested by challenge test, the survival rate (SR) and the relative percent survival (RPS) offish within 7 days was observed. There was no difference in the antibody level of mothers, eggs soluble extract, and the body fluid of fry at 5, 10 and 15 DPH from vaccinated mothers at one or two weeks after spawning. However, antibody of mothers, eggs and fry from vaccinated mothers at the dosage of 0,4 ml/kg body weight were higher than the dosage of 0,2 ml/kg body weight and control. Antibody titre. of fry of vaccinated mothers at 5, 10 and 15 DPH were (-log2=2,88), (-log2=2,53) and (-log2=2,07) respectively, while SR were 89%, 94% and 92% respectively. SR of control fry were lower 7%, 10% and 12% respectively than fry from vaccinated mother; meanwhile RPS were 47%. 76% and 77% respectively. Key words: Maternal immunity. Streptococcus iniae, Oreochromis niloticus, vaccination, antibody   ABSTRAK Suatu studi tentang efikasi dari dosis dan waktu pemberian vaksin pada vaksinasi lewat induk dilakukan. Induk ikan nila (Oreochromis niloticus) diberi vaksin melalui injeksi intraperitoneal dengan "adjuvant-heat killed Streptococcus iniae" satu minggu sesudah memijah dan dua minggu sesudah memijah dengan dosis 0,2 ml/kg dan 0,4 ml/kg bobot tubuh. Aglutinasi titer antibodi dari plasma darah induk sebelum dan sesudah memijah, ekstrak terlarut telur, dan cairan tubuh pada 5, 10 dan 15 hari setelah menetas (DPH) diperiksa. Imunitas dari larva diuji dengan uji tantang, kelangsungan hidup (SR) dalam 7 hari setelah uji tantang diamati. Hasil menunjukkan bahwa tidak ada perbedaan pada level antibodi dari induk, ekstrak terlarut telur dan cairan tubuh dari larva pada 5, 10 dan 15 DPH dari induk yang diberi vaksin pada satu atau dua minggu setelah memijah. Akan tetapi, level antibodi induk, ekstrak terlarut telur dan cairan tubuh larva dari induk-induk yang diberi vaksin dengan dosis 0.4 ml/kg bobot tubuh lebih tinggi dari 0.2 ml/kg bobot tubuh dan kontrol. Level antibodi dari larva yang berasal dari induk yang diberi vaksin dengan dosis 0.2 ml/kg, 0.4 ml/kg dan kontrol adalah (-log2=2.5), (-log2=2.9) dan (-log2=2). Sedangkan kelangsungan hidupnya masing-masing 95%, 94% dan 84%. Kata kunci: Imunitas induk. Streptococcus iniae, Oreochromis niloticus, vaksinasi, antibodi